2015
DOI: 10.5112/jjlp.56.250
|View full text |Cite
|
Sign up to set email alerts
|

Voice Changes over Time in a Female-to-Male Transsexual Receiving Hormone Therapy

Abstract: Objective: To characterize voice changes over a period of 143 days in a femaleto-male transsexual subject receiving hormone therapy.Patients and Methods: The subject was a 24-year-old female-to-male transsexual. Vocal assessment consisted of examination of the mean fundamental frequency (MF0), vocal range, the subject's impression concerning her own voice, and self-evaluation using the VHI scale.Results: MF0 started to decline after 48 days of therapy, and by 143 days it had descended 山王病院リハビリテーションセンター 1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Estrogen treatment in TGD people has not been associated with measurable voice changes (Mészáros et al., 2005 ), while testosterone treatment in TGD people has been found to result in both desired and undesired changes in gender- and function-related aspects of voice production (Azul, 2015 ; Azul et al., 2017 , 2018 , 2020; Azul & Neuschaefer-Rube, 2019 ; Cosyns et al., 2014 ; Damrose, 2008 ; Deuster, Di Vicenzo et al., 2016; Deuster, Matulat et al. 2016 ; Hancock et al., 2017 ; Irwig et al., 2017 ; Nygren et al., 2016 ; Van Borsel et al., 2000 ; Yanagi et al., 2015 ; Ziegler et al., 2018 ). Desired changes associated with testosterone treatment include lowered voice pitch, increased male attributions to voice, and increased satisfaction with voice.…”
Section: Chapter 14 Voice and Communicationmentioning
confidence: 99%
“…Estrogen treatment in TGD people has not been associated with measurable voice changes (Mészáros et al., 2005 ), while testosterone treatment in TGD people has been found to result in both desired and undesired changes in gender- and function-related aspects of voice production (Azul, 2015 ; Azul et al., 2017 , 2018 , 2020; Azul & Neuschaefer-Rube, 2019 ; Cosyns et al., 2014 ; Damrose, 2008 ; Deuster, Di Vicenzo et al., 2016; Deuster, Matulat et al. 2016 ; Hancock et al., 2017 ; Irwig et al., 2017 ; Nygren et al., 2016 ; Van Borsel et al., 2000 ; Yanagi et al., 2015 ; Ziegler et al., 2018 ). Desired changes associated with testosterone treatment include lowered voice pitch, increased male attributions to voice, and increased satisfaction with voice.…”
Section: Chapter 14 Voice and Communicationmentioning
confidence: 99%
“…Estrogen treatment in TGD people has not been associated with measurable voice changes (Mészáros et al, 2005), while testosterone treatment in TGD people has been found to result in both desired and undesired changes in genderand function-related aspects of voice production (Azul, 2015;Azul et al, 2017Azul et al, , 2018Azul et al, , 2020Azul & Neuschaefer-Rube, 2019;Cosyns et al, 2014;Damrose, 2008;Deuster, Di Vicenzo et al, 2016;Deuster, Matulat et al 2016;Hancock et al, 2017;Irwig et al, 2017;Nygren et al, 2016;Van Borsel et al, 2000;Yanagi et al, 2015;Ziegler et al, 2018). Desired changes associated with testosterone treatment include lowered voice pitch, increased male attributions to voice, and increased satisfaction with voice.…”
Section: Chapter 14 Voice and Communicationmentioning
confidence: 99%